MODIFIKASI PENETASAN TELUR BURUNG MALEO GUNUNG (Aepypodius arfakianus) UNTUK MENINGKATKAN DAYA TETAS - Hotlan Manik; Tri Yuwanta; Kustono (Kustono) (Buletin Peternakan, 2011)
his research aims to determine the physical characteristics and quality of eggs of mountain Maleo bird (Aepypodius arfakianus) in Papua and to determine hatching rate by using some modified hatching method to improvethe egg’s hatchability. This research used observation method to analyze variable egg hatching, temperature and humidity. There were three experiments of hatching method, which were semi-natural hatching outside of the habitat(ex-situ), hatching by using soil and serasah as the media, and hatching by using electric shelves as the media. Observation data of natural hatching showed that the temperature inside of the nest was about 30-35oC with humidityof 70-90%. The variables measured were embryo durability or fertility, hatchability, period of incubation, hatch weight, and embryo mortality. The data were analyzed using descriptive statistics and correlations for some data required and was presented as mean values and standard deviation (SD). Hatching using electric shelves as the media showed the best result. Length of incubation, egg fertility, hatchability, embryo mortality and hatch weight were 40.14±0.69 days,90.00%, 77.78%, 22.22%, 112.94±7.84 g, respectively; those of ex-situ modification were 47.50±0.71 days, 80%, 25%, 75%, 109.05±2.33 g, respectively; and those of soil and serasah media were 41.33±0.58 days, 90%, 33.33%, 66.67%, 113.33±5.05 g, respectively. Hatching modifications using electric shelves improves the quality of hatching, shorten theperiod of incubation, and reduced the mortality.(Keywords: Mountain Maleo (Aepypodius arfakianus), Hatching modification, Hatchability)